Cyclin A/B RxL macrocyclic inhibitors to treat cancers with high E2F activity - Singh, S; Gleason, CE; Fang, M; Laimon, YN; Khivansara, V; Xie, S; Durmaz, YT; Sarkar, A; Ngo, K; Savla, V; Li, Y; Abu-Remaileh, M; et al. (2024)
Cancer cell proliferation requires precise control of E2F1 activity; excess activity promotes apoptosis. Here, we developed cell-permeable and bioavailable macrocycles that selectively kill small cell lung cancer (SCLC) cells with inherent high E2F1 activity by blocking RxL-mediated interactions of cyclin A and cyclin B with select substrates. Genome-wide CRISPR/Cas9 knockout and random mutagenesis screens found that cyclin A/B RxL macrocyclic inhibitors (cyclin A/Bi) induced apoptosis paradoxically by cyclin B- and Cdk2-dependent spindle assembly checkpoint activation (SAC). Mechanistically, cyclin A/Bi hyperactivate E2F1 and cyclin B by blocking their RxL-interactions with cyclin A and Myt1, respectively, ultimately leading to SAC activation and mitotic cell death. Base editor screens identified cyclin B variants that confer cyclin A/Bi resistance including several variants that disrupted cyclin B:Cdk interactions. Unexpectedly but consistent with our base editor and knockout screens, cyclin A/Bi induced the formation of neo-morphic Cdk2-cyclin B complexes that promote SAC activation and apoptosis. Finally, orally-bioavailable cyclin A/Bi robustly inhibited tumor growth in chemotherapy-resistant patient-derived xenograft models of SCLC. This work uncovers gain-of-function mechanisms by which cyclin A/Bi induce apoptosis in cancers with high E2F activity, and suggests cyclin A/Bi as a therapeutic strategy for SCLC and other cancers driven by high E2F activity.